Informed Contraceptive Decisions: A Qualitative Study of Hispanic Teens in New Mexico - Mayra Perez; Stephanie Chambers; Venice Ceballos; Allyson Kelley; Jennifer Hettema; Andrew Sussman; Sally Kosnick; Evangelina Moralez-Norris; Samantha Jackson; Melanie Baca (Women's Health Reports, 2022)
Objectives: U.S. Hispanic teens experience higher rates of unintended pregnancy than white teens. Limited research has been done to explore the sociocultural factors that impact Hispanic teens and their decisions about birth control and long-acting reversible contraception (LARC). The theory of planned behavior served as a framework for this study and teen perspectives about contraceptive decision making. This study aimed to identify the sociocultural factors that impact Hispanic teens when they make decisions about birth control and LARC. Study Design and Methods: We interviewed Hispanic teens from school-based health centers in New Mexico during their schedule medical appointments. Interviews were audio recorded, transcribed, and coded using content analysis coding methods and a descriptive qualitative design. Results: A total of 20 Hispanic teens participated in this study, all were female and between the ages of 14 and 19 years. Themes: Five themes emerged from the analysis process that impact Hispanic teen contraceptive choice, these are family, religion, culture, peer influence, and other factors. Conclusions and Implications: Among both LARC and non-LARC groups, peer influence was the most frequently cited reason for contraceptive decision making. Relationships with family were cited as barriers for Hispanic teens, where lack of communication and abstinence-only beliefs made it difficult to seek contraception. Findings demonstrate that teens selected LARCs because of the impacts on menstrual cycles and clinician influence. Teens who did not self-select LARC discussed ease of protection and the utilization of birth control as a transition to LARC.